A dietary study of a family of four - Smith, Grace (My University, 1908)
Introduction: The object of this experiment was to consider the cost, caloric value, and nutritive ratio of the ordinary, every-day-diet of a family of four for one month. The materials were weighed as purchased, and a complete list kept, together with the cost of each.
Citation: Smith, Grace. A dietary study of a family of four. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Diet; Nutrition; Food; Graduating theses; Senior theses; Theses